Proposed Marketing Strategy for PINISI Hotel - Putriamalia, Livia; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2014)
Abstract.Bandung is known as the one of the cities in Indonesia, rich in tourism objects that are able to attract tourists (international and domestic) from year to year. The presence of trade and services sector has increased significantly compared to other sectors. This condition proves the hospitality business in Bandung is still profitable. Pinisi Hostel is a hostel that located in Bandung. As a new entrant, there are various issues that hit the Pinisi Hostel, such as not well known yet and stagnant occupancies rate, the demand high only on the weekend or holiday. The purpose of this study is to give solution for Pinisi Hostel, so that Pinisi Hostel can increase its sales. Some solutions that provided can be useful and give an input and also can used as a marketing strategy to increase sales for Pinisi Hostel. The resulting business solution is renew Segmenting, Targeting and Positioning as a basis of establishment of Pinisi Hostel marketing strategy. Then the marketing strategy recommendation applied to the form of the Marketing Mix.Key words: tourism objects, hospitality business, Bandung, marketing strategy